Assessment of hydrological connectivity characteristics of riparian zones and their correlation with root–soil composites at different bank heights of a first-class river in China - Yang, Qihong; Zhang, Chaobo; Liu, Xiaoguang; Yao, Shiming; Huang, Renyong (Frontiers in Ecology and Evolution, 2023)
Under the combined effects of topography and vegetation, hydrological connectivity characteristics of riverbank slopes become complex and unclear, which limit the utilization and protection of riparian zones. To quantify the hydrological connectivity in root–soil composites, we conducted dyeing and tracing experiments in a high elevation plot and a low elevation plot on the bank of the Fenhe River. Soil and root properties and hydrological connectivity indexes in the plots were measured and analyzed. The results showed that the soil dyeing area ratio was approximate 1 in the soil depth of 0–5 cm and then decreased to 0.1 from 5 cm to 25 cm. The dyeing area ratio, maximum dyed depth, length index, peak value and non-uniformity coefficient of the high plot (Pc2) were 27%, 26%, 5%, 40% and 45% greater than those of the low plot (Pc1). The index of hydrological connectivity (IHC) of Pc2 was 7%, 44% and 71% greater than Pc1 in the soil depths 0–10 cm, 10–20 cm and 20–30 cm respectively. There was no significant correlation between the IHC and the physical properties of the soil at different depths, and the soil hydrological connectivity was closely related to the plant roots with diameter less than 1mm. The study primarily explored the characteristics of hydrological connectivity in root–soil composites. The results provide a scientific basis for exploring hydrological connectivity of riparian zones, which can support future riparian zone protection and restoration efforts in similar regions.